Suporte social de cuidadores de pacientes com câncer de mama em quimioterapia: utilização da entrevista motivacional - Mourão, Carla Monique Lopes (2016)
Understanding the emotional impact of the diagnosis and treatment of breast cancer cause in women and the identification and encouragement of supportive relationships and help, can reflect the comprehensive care to women with breast cancer. The development of intervention strategies for the caregivers of patients with breast cancer chemotherapy tends to enable the development of more appropriate ways to meet the needs of this clientele. This study aimed to evaluate the effects of motivational interviewing for the change of social support behavior with the caregivers of patients with breast cancer undergoing chemotherapy. Study quasi-experimental, before and after conducted with 18 women undergoing chemotherapy for breast cancer in the Integrated Regional Oncology Center, Fortaleza-CE, and 18 caregivers of their women interviewed. The intervention was the Interview Brief Motivational (EMB) applied to 18 caregivers indicated by patients in four individual sessions at weekly intervals and duration of approximately 30 minutes each. The social support behavior was evaluated by women before and after the intervention by the Social Support Scale (ESS). socioeconomic questionnaires for women and caregivers were used. The results showed that social support of women showed high both for the emotional dimension as instrumental to the ESS after intervention used with caregivers (EMB). The results in the correlations between satisfaction with social support and the variable "sex", "lies with the patient", "age" and "education" with the answers of the same after the intervention showed no difference between the values ​​obtained the two dimensions of social support with respect to the variables (p> 0.05). In all comparisons was not possible to detect differences between the categories and answers after the intervention, so the result was the same regardless of sex, to reside with the patient, age and education, all with increased satisfaction with the support received. These results contribute to the clinical practice of several professional categories, not only the nurse, to use low-cost intervention strategies to improve the quality of life during and after treatment of women with breast cancer and promote health stimulating the adoption of instrumental and emotional social support individualized, personalized and focused on the patient and caregiver needs. This study concludes that the intervention used, the EMB, promoted a positive behavioral change to improve the social support provided by caregivers to patients with breast cancer and undergo chemotherapy.